Electrometric investigations on the system acid-molybdate and the formation of heavy metal molybdates - Prasad Shiva; Guimarães Thalma L.M. (Journal of the Brazilian Chemical Society, 1998)
The precise nature of the polyanions formed by the action of hydrochloric acid on sodium molybdate solutions has been studied by pH and conductometric measurements involving glass electrode and conductometric titrations. The inflections and breaks in the titration curves indicate the formation of para-Mo7O24(6-) and octa-Mo8O26(4-) polymolybdate anions around pH 5.5 and 4.1, corresponding to the molar; ratio 8H:7Mo and 3H:2Mo, respectively. Similar pH and conductometric titrations between Hg2 + and MoO4(2-), Mo7O24(6-), and Mo8O26(4-) provide definite evidence for the formation of normal molybdate HgO.MoO3, paramolybdate 3HgO.7MoO3 and octamolybdate 2HgO.8MoO3 of mercury(II) in the vicinity of the pH 4.9, 4.2 and 3.7, respectively. The analytical investigations of the precipitates of mercuric molybdates have also been carried out, which substantiate the results of the electrometric study.